Osmotic gradients and transretinal water flow—a quantitative elemental microanalytical study of frozen hydrated chick eyes - Marshall, Alan T.; Crewther, Sheila G. (Frontiers in Cellular Neuroscience, 2022)
Abstract Optical clarity and efficient phototransduction are necessary for optimal vision, however how the associated processes of osmoregulation and continuous fluid drainage across the whole eye are achieved remains relatively unexplored. Hence, we have employed elemental microanalysis of planed surfaces of bulk frozen-hydrated chick eyes to determine the unique intracellular elemental localization, compositions and hydration states that contribute to maintaining osmotic gradients and water flow from the vitreous, across the retina, retinal pigment epithelium (RPE), to choroid and sclera. As expected, the greatest difference in resultant osmotic concentration gradients, [calculated using the combined concentrations of sodium (Na) and potassium (K)] and tissue hydration [oxygen-defined water concentration], occurs in the outer retina and, in particular, in the RPE where the apical and basal membranes are characterized by numerous bioenergetically active osmoregulating ion transport mechanisms, aquaporins and chloride (Cl) channels. Our results also demonstrate that the high intracellular Na+ and K+ concentration in the apical region of the RPE are partially derived from the melanosomes. The inclusion of the ubiquitous osmolyte taurine to calculation of the osmotic gradients suggests a more gradual increase in osmotic transport of water from the vitreous into the ganglion cell layer across the inner retina to the outer segments of the photoreceptor/apical RPE region where the water gradient increases rapidly towards the basal membrane. Thus transretinal water is likely to cross the apical membrane from the retina into the RPE cells down the Na+ and K+ derived osmotic concentration gradient and leave the RPE for the choroid across the basal membrane down the Cl- derived osmotic concentration gradient that is sustained by the well described bioenergetically active RPE ion transporters and channels.